Four-Year Cost-Utility Analyses of Sealed and Nonsealed First Permanent Molars in Iowa Medicaid-Enrolled Children - Patita Bhuridej, DDS, MS, PhD; Raymond A. Kuthy, DDS, MPH; Stephen D. Flach, MD, PhD; (Blackwell Synergy, 2007)
Dental sealants, by their ability to prevent caries and maintain teeth in better health, have some inherent utility to individuals, programs, or society.